8t-9+4t=59-5t

Simple and best practice solution for 8t-9+4t=59-5t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8t-9+4t=59-5t equation:


Simplifying
8t + -9 + 4t = 59 + -5t

Reorder the terms:
-9 + 8t + 4t = 59 + -5t

Combine like terms: 8t + 4t = 12t
-9 + 12t = 59 + -5t

Solving
-9 + 12t = 59 + -5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '5t' to each side of the equation.
-9 + 12t + 5t = 59 + -5t + 5t

Combine like terms: 12t + 5t = 17t
-9 + 17t = 59 + -5t + 5t

Combine like terms: -5t + 5t = 0
-9 + 17t = 59 + 0
-9 + 17t = 59

Add '9' to each side of the equation.
-9 + 9 + 17t = 59 + 9

Combine like terms: -9 + 9 = 0
0 + 17t = 59 + 9
17t = 59 + 9

Combine like terms: 59 + 9 = 68
17t = 68

Divide each side by '17'.
t = 4

Simplifying
t = 4

See similar equations:

| x+7=31 | | (x+14)+(3x-18)=180 | | (9x+2)+(2x)=90 | | 7(7-1*1)=42 | | 9(7t+6)=306 | | 15-10t+7+8t= | | -4(x+3)(x+3)+5=-8 | | 7x-7x-1=42 | | 68-5= | | x^2+19x+29=5x-4 | | x^2+4x=-7 | | x^2+2x-34=1 | | (13-b)4=(2-0.5b)6 | | x-24.3=-6 | | -12=4m+8 | | 4t+22=90 | | 3z+2=(z-3)+9 | | (x-3)(-15)= | | 9m-3(2m-3)=11 | | -(67r+67s-94)= | | 2x+8=-24 | | 5+14-2w=9-(4w+2) | | 45+0.20m=66 | | 11x-4=56-x | | 25.24=5x+3.89 | | 4(x+15)=60 | | 2x-(3y+4z)= | | 117=-39x | | 12n+4-5n=42 | | 2z^2-9z-5=0 | | 42.55+0.20m=90 | | 4w-1=5w+37 |

Equations solver categories